(untitled) (UKLO Proceedings, 2026)
Introduction: Scientific communication is fundamental to advancing science, increasing visibility, and integrating science into society. In North Macedonia, there is a recognized need for systematic support for scientists and for an institutional framework that promotes quality peer review, transparent knowledge dissemination, and open access. Results: The Association was founded on June 10, 2025, by distinguished scientific professionals. Its mission is to ensure quality, visibility, and open access to Macedonian scientific output while aligning with international standards. The Association organizes training sessions, peer review workshops, seminars, conferences, and mentorship programs. Discussion: Through its activities, MASC plays a pivotal role in overcoming structural barriers in Macedonian science, promoting intersectoral and international cooperation, and empowering early-career researchers. It strengthens scientific culture, supports ethical research practices, and increases visibility of national research outputs.